POST-STROKE COGNITIVE IMPAIRMENT - PHENOMENOLOGY AND PROGNOSTIC FACTORS - Maya Danovska; Boyko Stamenov; Margarita Alexandrova; Dora Peychinska (Peytchinski Publishing, 2012)
Stroke patients are at higher risk of developing cognitive impairment. Cognitive dysfunctions, especially progressive ones, worsen stroke prognosis and outcome. A longitudinal follow-up of cognitive disorders, however, is rendered difficult by their heterogeneity and the lack of definitions generally agreed upon. Stroke is a major cause of cognitive deficit. The identification of risk factors, clinical determinants and laboratory markers of post-stroke cognitive deficit may help detect patients at increased risk of cognitive deterioration, and prevent or delay the occurrence of post-stroke cognitive impairments. Though inflammatory processes have been implicated in the pathogenesis of stroke, their role in the complex pathophysiological mechanisms of post-stroke cognitive impairment is not completely understood. Evidence suggests that elevated serum C-reactive protein is associated with both the increased risk of stroke and post-stroke cognitive deficit. The hypothesis of a possible relationship between markers of systemic inflammation and cognitive dysfunctions raises the question of how rational the option of applying non-steroidal anti-inflammatory drugs in a proper therapeutic window will be, especially during the acute phase of stroke, to prevent cognitive decline and dementia.